2016
DOI: 10.1515/ijfe-2015-0296
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on the Drying Behavior and Quality of Citrus Peels

Abstract: The effects of the drying temperature and the residual moisture content on the drying behavior, energy consumption and quality of dried citrus peels (CPs), which are value-added food ingredients, were studied. The CP samples were dried in a laboratory-scale hot-air dryer at air temperatures from 40 to 70 °C under a constant air velocity of 1 m/s until the desired moisture content for safe storage was reached or until the final moisture level was achieved for the specific drying conditions. Cakes prepared from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…It took 180 min, 240 min, 300 min, and 360 min to achieve MC s of 3.64%, 7.18%, 7.34%, and 7.06%, respectively, at HAD temperatures of 50°C, 60°C, 70°C, and 80°C, respectively, from the HP’s initial MC of 74.6%. Previous research has reported that oven drying of mandarin and orange peels, required 360–540 min and 300–420 min, respectively, (Marey & Shoughy, 2016). Thus, the high drying temperature in this study increased the drying rate, thereby shortening the length of time required to dry the HP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It took 180 min, 240 min, 300 min, and 360 min to achieve MC s of 3.64%, 7.18%, 7.34%, and 7.06%, respectively, at HAD temperatures of 50°C, 60°C, 70°C, and 80°C, respectively, from the HP’s initial MC of 74.6%. Previous research has reported that oven drying of mandarin and orange peels, required 360–540 min and 300–420 min, respectively, (Marey & Shoughy, 2016). Thus, the high drying temperature in this study increased the drying rate, thereby shortening the length of time required to dry the HP.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 1b, the curve of the drying rate of HP during the initial drying stage clearly rose and, subsequently, dropped as the HAD time increased. However, the abovementioned study of the oven drying of citrus peel reported only the phase in which the drying rate fell (Marey & Shoughy, 2016). This difference in the drying rate curve indicates a different mechanism of water transfer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ascorbic acid can be easily degraded depending on various factors like temperature, drying time, moisture content, air velocity, sample geometry, the presence of enzyme, oxygen and metallic catalysts. (5) Considering the drying temperatures in the range from 40°C to 80°C, the higher the drying temperature, the greater ascorbic acid losses have been observed for many plant-based products (8,15,19,36,43); however, AA content may also increase when dried at 50°C as was observed in salak fruit (9), tomato slices (40) and pears. (37) Gamboa-Santos et al 7found similar amount of ascorbic acid in strawberries after drying at 40°C and 50°C for 7 h. The initial moisture content of the products plays a key role during the thermal degradation of ascorbic acid.…”
Section: Meta-analysismentioning
confidence: 99%
“…To inactivate enzymatic reactions during processing, blanching is generally carried out before drying [14]. Marey and Shoughy [15] reported that quick drying is very essential to reduce the moisture content to a safe level previous to further processing because of the high moisture content of the citrus residuals after processing.…”
Section: Introductionmentioning
confidence: 99%